Motivational patterns defined by cluster analysis and their relationship with perceived ability and academic achievement - Rodríguez Ayán, María Noel (Anales de Psicología / Annals of Psychology, 2010)
The purpose of this study is to identify motivational patterns of Uruguayan University students using cluster analysis in an attempt to confirm the three-cluster structure described in previous research and to compare the perceived ability and academic achievement of the different groups. Participants were 1573 students of Chemistry careers that com-pleted the personal tendencies scale developed by T. Hayamizu and B. Weiner (1991) and the Smart scale developed by P. Trapnell (1994). Grades and career progress were employed as measures of academic achievement. To compare the differences of achievement among clusters a subgroup of 587 students who had passed at least one course in the last 2 years was selected. Results suggest 3 motivational patterns: one simul-taneously oriented towards learning and performance goals (multiple orientation); one exclusively oriented towards learning goals (learning orientation) and one with very low motivation. The 3 clusters differed significantly on perceived ability (p<.001), with the multiple orientation cluster having the highest value, followed by the learning oriented group. Multiple and learning oriented clusters did not differ significantly on academic achievement (p=.750, grades; p=.861, progress), which was higher (p<.001) than third cluster’s achievement.